Sostenible o Sustentable - Alvarado Vázquez, Marco A.; Salcedo Martínez, Sergio M.; Vargas López, Victor Ramón (Universidad Autónoma de Nuevo León, 2024)
Sostenible o sustentable, un tema para reflexionar si ambos términos nos dicen lo mismo.